Supporting the Transformation of Livelihoods: Village Development Funds Managed by Self-Help Groups - Gonsalves, Julian Francis; Soria, Giulia; Or, Thy; Yim, Soksophors; Tong, Chantheang; Tath, Sok (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2019)
This primer is used to train, monitor, and coach communities implementing the Biodiversity Conservation Corridors Project (BCCP) in Cambodia on Village Development Funds, which aims to help villages effectively achieve better livelihoods and infrastructures in their communities.